Public space and vibrant ground-floor zones in sustainable city-quarter development: Learning from the smart-city Graz. - Degros, Aglaée; Rainer, Ernst; Grabner, Martin; Konrad, Oliver (Springer, 2018)
The present paper builds upon the basis that a sustainable city is fundamentally determined by its built structure. Attractive public space contributes decisively to the quality of life, which is the overall goal of sustainable development. This paper focuses specifically on the role of the ground-floor zone as a factor for a lively public space and points out the importance of the interrelationship between the public space and the ground floors of the adjacent buildings, while also discussing the necessary qualities and strategies to be achieved. The paper briefly presents the research and realization project Smart City Graz, which is seeking to develop new knowledge and models of integrated and holistic city planning and development processes. An urban-framework plan and demonstration projects are developed in a comprehensive stakeholder process to initiate the development of a new quarter in the city of Graz, the Smart City Graz Waagner Biro. Informal instruments completing the traditional planning instruments were introduced in the development process to meet these challenges: the framework plan, town planning, architecture and public-space competitions, accompanied by private-law contracts, and the development of a monitoring concept. Particular emphasis is put on the functional and spatial requirements for buildings' ground-floor zones to prepare the way for a successful intertwining of the exterior and the interior as the basis for a vibrant public space and through this, for a lively city quarter. Furthermore, the question of the programming of the ground-floor uses on the scale of a city quarter or street is addressed. The municipality as the representative of the public must protect common interests and guarantee public benefits that go beyond the individual economic interests of the various stakeholders.
Keywords: Stadterweiterung; Stadtteilentwicklung; Stadtentwicklungskonzept; Smart City; Öffentlicher Raum; Nachhaltigkeit; Funktionsmischung; Erdgeschoss